Clinical observation of peripheral nerve injury in 2 patients with cancer after radiotherapy - Zhang, Zhao-hui; Liang, Li; Jia, Ting-zhen; Zhang, Shu-lan; Wang, Mo-pei; Ma, Li-Wen; Liu, Qiang (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : This study aims to analyze the clinical manifestations and sequelae of peripheral nerve radiation damage of two cases of cancer patients after radiotherapy at the corresponding sites in clinical practice and to summarize experiences and lesions in order to provide a reference for future tumor radiotherapy. Material and methods : Some data of two cases of patients, such as doses of radiotherapy, clinical manifestations and damage occurrence time, were collected and examinations were conducted to define diagnosis. Afterwards, therapies and follow-up were conducted. Results: Case 1 (rectal cancer) was diagnosed as mild left lower extremity nerve damage. After the symptomatic treatment, the disease condition was improved, and there was no tumor recurrence sign. Case 2 (breast cancer) was diagnosed as left brachial plexus damage, and left upper extremity movement function was lost completely. While the analgesic treatment was conducted, anti-tumor relevant treatments were being carried out. Conclusions : Radiotherapy can cause different extents of radioactive nerve damage. In practice, it is necessary to constantly improve the radiotherapy technology level and actively prevent the occurrence of complications. Once symptoms appear, the diagnosis and treatment should be conducted as early as possible in order to avoid aggravating damage to cause dysfunction and cause lifetime pain to patients.